PERCEPTION AND PREFERENCES OF HOSPITALITY MANAGEMENT STUDENTS TOWARDS WORKING IN HOTEL INDUSTRY - Kukreti, Ravish; Dani, Rakesh (International Journal of Psychosocial Rehabilitation, 2020)
The hospitality industry is a service industry which includes several sectors such as hotels, food industry, tourism, retail sector, event companies, theme parks, transportation and many more. The bang in hospitality and tourism sector is not only in India but abroad also has impressed it into a most of profitable and beneficial sector of the world that also brings a considerable amount of foreign exchange. As an affect many well- known hotel chains are planning to open a huge number of hotels throughout the world. To run their organization (hotel business), educated and expert manpower is required. This has triggered the hospitality education in the India too. The hospitality industry worldwide has been stood up to with the issue of pulling in and holding quality workers. On the off chance that the present understudies are to turn into the viable experts of tomorrow, it is crucial to comprehend their impression of the travel industry work. Along these lines, this study targets exploring the view of hospitality management students at the various schools in Uttrakhand towards the business as a lifelong decision. This research paper will focus on last year students who are going to join hotels in short duration. This research aimed to find the perception and preferences of hospitality management students towards working in hotel sector. This research paper is based on observation and feedback of 200 students of different colleges for which prearranged questionnaire along with the personal interview of selected students which included 20 well framed questions analyzed of likert scale statistical tools such as percentage and mean from which we conclude that perception of final year hospitality management students towards their preferences and choices to work in reputed hotel brands industry